Law, State and Telecommunications: the year the spectrum shrank, again - Board, Editorial (Law, State and Telecommunications Review, 2010)
This text introduces the Law, State, and Telecommunications Review, addressing, by way of an overview, its structure, contents and editorial policy. Besides that, this introduction defines the underpinnings of the journal’s regulatory approach. Statutes, administrative regulation and judicial decisions of 2009 pertaining to telecommunications are referred to in detail. It also addresses the main political and juridical discussions about the Brazilian telecommunications sector that took place the year before the publication of the journal’s volume.